Role of modifiable risk factors in the development of cognitive impairment in hypertensive patients - V. Skybchyk; O. Peleshko (Kazimierz Wielki University, 2019)
Background. The prevalence of all types of cognitive impairment, including dementia, is increasing but knowledge of aetiological factors is still evolving. This study aimed to analyze the state of cognitive functions in hypertensive patients and evaluate the role of risk factors in their occurrence. Materials and methods. We examined 89 patients (1-st group; middle age of patients was 51,1 ± 7,3 years; 53,9% of men) with stage 2 hypertension and 30 practically healthy people (2-nd group; middle age of individuals was 41,4 ± 10,1 years; 56,7% of men) with normal level of blood pressure. Cognitive tests included the General Practitioner assessment of Cognition (GPCOG), the Mini-Mental State Examination (MMSE), Schulte tables. Results. The average MMSE score was 26.5 ± 1.8 in the 1st group and 28.9 ± 1.0 in the 2nd group, that indicates a significant cognitive decline in hypertensive patients (p